Effects of increasing the availability of vegetarian options on main meal choices, meal offer satisfaction and liking: a pre-post analysis in a French university cafeteria - Laura Arrazat; Claire Cambriels; Christine Le Noan; Sophie Nicklaus; Lucile Marty (BMC, 2024)
Abstract Background Changing the food environment is an important public health lever for encouraging sustainable food choices. Targeting the availability of vegetarian main meals served in cafeterias substantially affects food choice, but acceptability has never been assessed. We examined the effects of an availability intervention at a French university cafeteria on students' main meal choices, meal offer satisfaction and liking. Methods A four-week controlled trial was conducted in a university cafeteria in Dijon, France. During the two-week control period, vegetarian main meals constituted 24% of the offer. In the subsequent two-week intervention period, this proportion increased to 48%, while all the other menu items remained unchanged. Students were not informed of the change. Student choices were tracked using production data, and daily paper ballots were used to assess student satisfaction with the meal offer and liking of the main meal they chose (score range [1;5]). Nutritional quality, environmental impact, and cost of production of meal choices were calculated for each lunchtime. Food waste was measured over 4 lunchtimes during control and intervention periods. An online questionnaire collected student feedback at the end of the study. Results Doubling availability of vegetarian main meals significantly increased the likelihood of choosing vegetarian options (OR = 2.57, 95% CI = [2.41; 2.74]). Responses of the paper ballots (n = 18,342) indicated slight improvements in meal offer satisfaction from 4.05 ± 0.92 to 4.07 ± 0.93 (p = 0.028) and in liking from 4.09 ± 0.90 to 4.13 ± 0.92 (p < 0.001) during control and intervention periods, respectively. The end-of-study questionnaire (n = 510) revealed that only 6% of students noticed a change the availability of vegetarian main meals. The intervention led to a decrease in the environmental impact of the main meals chosen, a slight decrease in nutritional quality, a slight increase in meal costs and no change in food waste. Conclusions Doubling availability of vegetarian main meals in a university cafeteria resulted in a twofold increase in their selection, with students reporting being more satisfied and liking the main meals more during the intervention period. These results suggest that serving an equal proportion of vegetarian and nonvegetarian main meals could be considered in French university cafeterias to tackle environmental issues. Trial registration Study protocol and analysis plan were pre-registered on the Open Science Framework ( https://osf.io/pf3x7/ ).